1994
DOI: 10.2134/agronj1994.00021962008600020017x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Carbon Dynamics in No‐Till and Stubble Mulch Tillage Systems

Abstract: Soil nitrogen and organic carbon differences between no‐till and conventional tillage systems are often dramatic and well documented, but these differences between no‐till and stubble mulch tillage systems are more subtle. Our objective was to evaluate changes in soil inorganic N, organic N, organic C, surface soil moisture and grain yield on the southern High Plains as affected by stubble mulch and no‐till tillage systems from 1988 to 1992. The cropping system was a sorghum (Sorghum bicolor (L.) Moench)‐sorgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…4), teores de C orgânico superiores em relação ao tratamento com exportação. Christensen et al (1994) observaram, após cinco anos de experimentação, que o teor de C orgânico foi superior no plantio direto, em comparação com o cultivo mínimo, e Sidiras & Pavan (1985) obtiveram maiores teores de C orgânico no sistema de vegetação permanente, o que mostra a importância dos resíduos vegetais sobre o solo. No tratamento com adubação orgânica, as forrageiras perenes (Sistemas I e II) foram superiores às anuais (Sistema III), mostrando, assim, que o ciclo da cultura teve maior influência que a produção de matéria seca.…”
Section: Resultados E Discussão Caracterização Química Do Solounclassified
See 1 more Smart Citation
“…4), teores de C orgânico superiores em relação ao tratamento com exportação. Christensen et al (1994) observaram, após cinco anos de experimentação, que o teor de C orgânico foi superior no plantio direto, em comparação com o cultivo mínimo, e Sidiras & Pavan (1985) obtiveram maiores teores de C orgânico no sistema de vegetação permanente, o que mostra a importância dos resíduos vegetais sobre o solo. No tratamento com adubação orgânica, as forrageiras perenes (Sistemas I e II) foram superiores às anuais (Sistema III), mostrando, assim, que o ciclo da cultura teve maior influência que a produção de matéria seca.…”
Section: Resultados E Discussão Caracterização Química Do Solounclassified
“…O efeito recuperador da adubação mineral e orgânica nas características químicas do solo em área degradada foi observado por Lucchesi (1988), Melo (1994) e Motta Neto (1995). A permanência do material vegetal sobre o solo tem proporcionado melhores níveis de fertilidade, conforme Sidiras & Pavan (1985), Havlin et al (1990), Bhat et al (1991), Testa et al (1992) e Christensen et al (1994).…”
unclassified
“…Jowkin and Schoenau (1998) report that N availability was not greatly affected in initial years by switching to no-till in the brown soil zone in Canada. Others report that conventional tilling systems accelerate organic matter mineralization, resulting in more nutrient availability than under notill (Christensen et al, 1994;Doran, 1980). Little is known about the effects of conventionally tilled vs permanent beds and residue management on C or N mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional no‐till practices focused more on reducing soil disturbance than on stubble management, but later studies emphasized more on the significance of residue cover. Christensen et al (1994b) reported that part of seed yield improvement of grain sorghum under no‐till can be attributed to the moisture savings from the previous season's crop residue.…”
Section: Tillage and Stubble Managementmentioning
confidence: 99%